Autonomous, atypical, hybrid forms of employment: Aspects of social protection in Italy. National report - Marcello Pedaci; Dario Raspanti; Luigi Burroni (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2017)
In many European countries, marginal part-time, (solo-) self-employment and secondary jobs has been increasing since the last decades. The question about the provision of social protection and labour legislation for these types of employment is the starting point for a project entitled "Hybrid working arrangements in Europe", directed by the WSI. Germany, Great Britain, the Netherlands, Poland, Italy, Denmark and Austria comprise the group of countries selected in order to investigate "hybrid work" in the context of different welfare state regimes. The following paper by Marcello Pedaci, Dario Raspanti and Luigi Burroni is one of the seven country studies that describe in detail labour law regulations and the national insurance systems for self-employed, secondary jobs and marginal part-time employment.
urn:nbn:de:101:1-201802215352
Keywords: 330